DOI: 10.4995/thesis/10251/78215
|View full text |Cite
|
Sign up to set email alerts
|

Modelación De La Calidad De Las Aguas en Los Humedales Artificiales De Flujo Superficial (Hafs). Aplicación a Los Hafs Del Tancat De La Pipa en l'ALBUFERA De Valencia.

Abstract: Capítulo 8.Comparación de la simulación de las formas de fósforo en los dos capítulos anteriores .. 201Capítulo 9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 155 publications
(278 reference statements)
0
1
0
Order By: Relevance
“…Indeed, when the rainfall was lower, the residence time of the water in the wetland increased, which possibly allowed a greater self-purification effect, that favored the trophic recovery of this aquatic ecosystem. Gargallo [58], García et al [59], and Kadlec and Wallace [51] indicated that by increasing flow, vegetation cover, and HRT, it was possible to increase the TP mass removed in wetlands. Alasino et al [60] also reported that water bodies with high hydrodynamic renewal (i.e., reduced residence times) tended to impede the development or restoration of biogeochemical cycles, which adversely affected the wetland.…”
Section: Tsi Analysismentioning
confidence: 99%
“…Indeed, when the rainfall was lower, the residence time of the water in the wetland increased, which possibly allowed a greater self-purification effect, that favored the trophic recovery of this aquatic ecosystem. Gargallo [58], García et al [59], and Kadlec and Wallace [51] indicated that by increasing flow, vegetation cover, and HRT, it was possible to increase the TP mass removed in wetlands. Alasino et al [60] also reported that water bodies with high hydrodynamic renewal (i.e., reduced residence times) tended to impede the development or restoration of biogeochemical cycles, which adversely affected the wetland.…”
Section: Tsi Analysismentioning
confidence: 99%